Effects of Gum Arabic-Coated Magnetite Nanoparticles on the Removal of Pb Ions from Aqueous Solutions - Hanan J. Mustafa; Tagreed M. Al-Saadi (Iraqi Journal of Science, 2021)
To study the removal of lead (Pb) ions from aqueous solutions, novel magnetite nanoparticles (NPs) of Ni0.31Mg0.15Ag0.04Fe2.5O4 were synthesized by coprecipitation synthesis using metal sulfates, and then coated with Gum Arabic (GA). The prepared NPs were analyzed using various spectroscopic and analytical methods, such as X-Ray diffraction analysis (XRD), Field Emission Scanning Electron Microscopy (FE-SEM), Energy Dispersive X-ray spectroscopy (EDX), Fourier Transform Infra-Red spectroscopy (FT-IR), and Atomic Absorption Spectrophotometer (AAS). By using XRD analysis, the cubic inverse spinel structure of the prepared NPs was proven, showing average values of crystallite size, lattice constant, and density of 28.57nm, 8.32582Å, and 5.2890 g/cm3, respectively. FE-SEM analysis revealed the sphere-like shape of the nanoparticles with a measured crystallite size of 25.93nm. The existence of constituent elements was evidenced by EDX. FT-IR test proved the success of the coating process of magnetite NPs by the presence of the main characteristic absorption bands of GA in the FT-IR spectrum of GA-magnetite NPs. The adsorption of Pb ions by GA- magnetite NPs was shown by AAS analysis, where the concentration of Pb ions decreased from 25ppm to 6.6ppm, reaching 1.1ppm at the time of 25min. The porosity of the NPs and the carboxyl groups in GA played an important role in the process.